Influence of Solvent and Lecithin in Microencapsulation of Fish Oil by Spray-Drying - Gimenez-Castillo, B (Royal Society of Chemistry, 2018)
Fish oil (FO) was encapsulated by conventional spray-drying (FO-W-Lec) and by ethanol spray-drying, with FO incorporated as an oil-in-ethanol emulsion (with lecithin as emulsifier, FO-EtOH-Lec) or as an oil-in-ethanol dispersion (without lecithin, FO-EtOH). FO-EtOH-Lec and FO-W-Lec were obtained according to a central composite design, whereas FO-EtOH was prepared under optimal conditions. The optimal FO/hydroxypropylcellulose ratio was 1:4 for all FO-systems, but the optimal inlet gas temperature was lower for FO-EtOH and FO-EtOH-Lec (135 °C) than for FO-W-Lec (200 °C). The encapsulation efficiency (EE) for ethanol spray-drying (FO-EtOH-Lec, 81.1% and FO-EtOH, 80.4%) was higher than conventional spray-drying (71.1%). However, the FO stability was better for FO-EtOH-Lec, measured either by total oxidation compounds or by polymerization compounds. The FO released in aqueous models corresponded only to surface FO in all FO-systems, showing Fickian diffusion. Ethanol spray-drying is an alternative to conventional methods, increasing the EE values of FO. Furthermore, lecithin allows improving the FO stability when incorporated as an emulsifier in ethanol spray-drying. © 2018 The Royal Society of Chemistry.